If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(n + -3) = bn Reorder the terms: a(-3 + n) = bn (-3 * a + n * a) = bn (-3a + an) = bn Solving -3a + an = bn Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Combine like terms: bn + -1bn = 0 -3a + an + -1bn = 0 The solution to this equation could not be determined.
| 5(x+7)+4=-5(x-1) | | h/9-1/2=5/18 | | 4x=13+4x | | 3x+7x*1=2(5x+1) | | (xy^2)(xy^2)(xy^2)= | | -38=2(u+8)-8u | | x+(x+26)=90 | | 5x+17=7+3x | | 9x/2=170 | | 9x+1-7x=.5(4x+2) | | x/3=2x-45 | | x/3=2x45- | | 2x-6=3/2(-2x-2) | | 2(3x-3+x-3)=2(2x-1)+2x | | .5h+.333(h-6)=.83333h+2 | | x/3=2x45 | | 3.402+6.5n=6.2n+5.1 | | n+4=3n-8 | | 4x^2-11x+20=0 | | -1326+646= | | X=624 | | 4.3r-7=3.3r-7 | | 2.564x=12.40976 | | 6+6n+5n=17 | | -4(2x+6)-12=4 | | -11-3x+8=-5x+14 | | -2k+6=28 | | -10=-8x+3x | | -0.10(85)+0.75x=0.05(x-2) | | -14=9x-5 | | -1/3(x-15)=-48 | | -1312-646= |